SL-6 Mimic Is a Biostimulant for Chlorella sorokiniana and Enhances the Plant Biostimulant Effect of Microalgal Extract - Daria Gabriela Popa; Naomi Tritean; Florentina Georgescu; Carmen Lupu; Sergey Shaposhnikov; Diana Constantinescu-Aruxandei; Florin Oancea (Plants)
This study aimed to evaluate the impact of a more cost-efficient strigolactone mimic SL-6 on Chlorella sorokiniana NIVA-CHL 176 growth in comparison with the strigolactone analog GR24 and the plant biostimulant functions of microalgal extracts. Three molar SL-6 concentrations were tested: 10−7 M, 10−8 M, and 10−9 M, respectively. Five parameters of microalgal growth were assessed: optical density, turbidity, biomass production, chlorophyll fluorescence, and pigment concentration. Results after 15 days of culturing revealed that the SL-6 treatments significantly enhanced biomass production (13.53% at 10−9 M), pigment synthesis, and photosystem II activity (14.38% at 10−9 M). The highest increases in pigments induced by SL-6 were 15.7% for chlorophyll a (at 10−8 M SL-6), 12.87% for chlorophyll b (at 10−9 M SL-6), 2.3% for carotenoids (at 10−8 M SL-6), and 10.78% for total pigments (at 10−8 M SL-6) per gram biomass compared to the solvent control (DMSO). Higher doses of GR24 and SL-6 (10−7 M) inhibited microalgal growth, reducing cell density, biomass production, and pigment synthesis. The microalgal extracts acted as plant biostimulants, stimulating root and shoot elongation and proton pump functioning of mung seedlings in the presence and absence of salt stress. The extracts from SL-6 biostimulated C. sorokiniana were more active as plant biostimulants than the extracts from the non-stimulated C. sorokiniana.